Educational Neuroscience and Reconsideration of Educational Research - Fride Roe Frobakk (Charles University, 2017)
Abstract: Educational neuroscience is a cross-disciplinary field where researchers work at the interface of education, psychology, and cognitive neuroscience. Certain difficulties arise in the merging of the disciplines due to the traditions differences in philosophies, methodologies, theories, and practices. Critical consideration of the 'bridging project' is essential for educational neuroscience's development, but I will also argue that questions arising in the wake of this cross-discipline can be relevant for reconsidering educational research. Keywords: Educational research, Educational neuroscience, Reconsideration, Transdisciplinary research.